2016
DOI: 10.1177/1354816616683051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hotel productivity growth in Balearic and Canary islands

Abstract: This article examines the productivity of hotels operating in the two main sun and sand tourism markets in Spain, the Balearic, and the Canary Islands, from 2004 to 2013. In this manner, we can evaluate the impact of the global economic crisis on this sector. To tackle this issue, we apply alternative Malmquist productivity index decompositions to distinguish between different components of productivity. The results reveal that the economic downturn had major negative effects on hotel productivity for 2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
6
10
0
Order By: Relevance
“…Following the relative literature of hotels’ efficiency and productivity measurements (Assaf & Agbola, 2014; Assaf & Barros, 2011; Assaf et al, 2011; Assaf & Josiassen, 2016; Cordero & Tzeremes, 2017; Tzeremes, 2019), we defined hotels’ production function having as inputs total employees and total fixed assets (measured in millions of euros). Moreover, our output is hotels’ total sales levels, which is also measured in millions of euros.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the relative literature of hotels’ efficiency and productivity measurements (Assaf & Agbola, 2014; Assaf & Barros, 2011; Assaf et al, 2011; Assaf & Josiassen, 2016; Cordero & Tzeremes, 2017; Tzeremes, 2019), we defined hotels’ production function having as inputs total employees and total fixed assets (measured in millions of euros). Moreover, our output is hotels’ total sales levels, which is also measured in millions of euros.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…An essential part of the Malmquist productivity index (MPI) is the estimation of distance functions (DFs). The DEA approach for estimating DFs is very popular among scholars when measuring hotels’ efficiency and productivity levels (Brown & Ragsdale, 2002; Cordero & Tzeremes, 2017; Dolasinski et al, 2019; Goncalves, 2013; Walheer & Zhang, 2018). The studies by Hwang and Chang (2003) and Barros and Alves (2004) were the first to apply the DEA-based MPI in order to measure and decompose the productivity of different hotel sectors.…”
Section: Introductionmentioning
confidence: 99%
“…This article considers also the possible scale effects in the productivity changes. Then, the decomposition suggested by Ray and Desli (1997) and recently applied for the first time in the hotel sector by Cordero and Tzeremes (2017) is adopted. The MPI can be rewritten as (Cooper et al, 2006: 215)…”
Section: Methodsmentioning
confidence: 99%
“…Cho and Wang (2017) adopted a cost metafrontier MPI model on Taiwan hotel industries and concluded that the international chain hotel is significantly superior to independent hotels. Cordero and Tzeremes (2017) applied the MPI approach to two main sun and sand tourism markets in Spain. They found that the economic downturn had major negative effects on hotel productivity in 2008 and 2009.…”
Section: Efficiency Productivity and Technological Change In Tourismentioning
confidence: 99%